2020
DOI: 10.1101/2020.10.19.343400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding diversity of Asgard archaea and the elusive ancestry of eukaryotes

Abstract: Comparative analysis of 162 (nearly) complete genomes of Asgard archaea, including 75 not reported previously, substantially expands the phylogenetic and metabolic diversity of the superphylum Asgard, with six additional phyla proposed. Phylogenetic analysis of universally conserved genes does not strongly support the origin of eukaryotes from within Asgard but rather, leans towards a three-domain topology, with eukaryotes branching outside archaea. Using sensitive methods for protein domains detection on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Our analysis confirms a patchy distribution of ESPs among asgardarchaea (Dacks et al 2016, Zaremba-Niedzwiedzka et al 2017, Imachi et al 2020, Liu et al 2020, Klinger et al 2016, Inoue et al 2020, Bulzu et al 2019) (Fig. 1).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our analysis confirms a patchy distribution of ESPs among asgardarchaea (Dacks et al 2016, Zaremba-Niedzwiedzka et al 2017, Imachi et al 2020, Liu et al 2020, Klinger et al 2016, Inoue et al 2020, Bulzu et al 2019) (Fig. 1).…”
Section: Discussionsupporting
confidence: 83%
“…To begin with, the iconic tree that introduced three aboriginal lineages (Woese and Fox 1977) might require a revision. Phylogenomic analysis of asgardarchaea provides evidence for a two-domains tree and the emergence of the host cell lineage of eukaryogenesis from within the archaeal domain (Cox et al 2008, McInerney et al 2014, Hug et al 2016, Williams et al 2020) with some skepticism, however, remaining (Forterre 2015, Da Cunha et al 2018, Liu et al 2020). Parallel to the discovery of the asgardarchaea were immediate speculations regarding their cellular complexity (Dacks et al 2016, Pittis and Gabaldón 2016, Rout and Field 2017, Akil and Robinson 2018, Zachar et al 2018, Neveu et al 2020) and a faith of having identified the missing link between pro- and eukaryotic biology based on the identification of a few e ukaryote s ignature p roteins (ESPs), that we find to be only 27 on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] Similarly, a recent study that significantly expanded Asgard diversity by sampling novel lineages also preferentially produced 3D trees when employing a range of sequence evolution models. [20] Despite these mixed results and underlying uncertainties in phylogenetic reconstruction, and the fact that the majority of Asgard genomes are derived from metagenome assemblies, several scientists claim that the 2D ToL model has now replaced the 3D model, contending that the debate is now settled. [13,21] Others argue the debate remains open [18][19][20]22] or support an alternative 2D tree with eukaryotes and prokaryotes as the two primary superkingdoms.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Despite these mixed results and underlying uncertainties in phylogenetic reconstruction, and the fact that the majority of Asgard genomes are derived from metagenome assemblies, several scientists claim that the 2D ToL model has now replaced the 3D model, contending that the debate is now settled. [13,21] Others argue the debate remains open [18][19][20]22] or support an alternative 2D tree with eukaryotes and prokaryotes as the two primary superkingdoms. [23] Here, we revisit the 3D versus 2D debate.…”
Section: Introductionmentioning
confidence: 99%